1997
DOI: 10.1038/sj.bjp.0701481
|View full text |Cite
|
Sign up to set email alerts
|

Hexamethonium‐ and methyllycaconitine‐induced changes in acetylcholine release from rat motor nerve terminals

Abstract: 1 The neuronal nicotinic receptor antagonists hexamethonium and methyllycaconitine (MLA) have been used to study the putative prejunctional nicotinic ACh receptors (AChRs) mediating a negativefeedback control of ACh release from motor nerve terminals in voltage-clamped rat phrenic nerve/ hemidiaphragm preparations. 2 Hexamethonium (200 mM), but not MLA (0.4 ± 2.0 mM), decreased the time constant of decay of both endplate currents (e.p.cs) and miniature endplate currents (m.e.p.cs), indicating endplate ion chan… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
27
0

Year Published

1998
1998
2022
2022

Publication Types

Select...
3
3

Relationship

1
5

Authors

Journals

citations
Cited by 21 publications
(28 citation statements)
references
References 37 publications
1
27
0
Order By: Relevance
“…These DMPP‐induced reductions probably reflect the appearance of a small degree of endplate ion channel block. However, given that the reductions in time constants of decay were small and similar for both MEPCs and EPCs, we consider it unlikely that the presence of this endplate ion channel block would have a significant impact on the quantal analysis of ACh release (see also Tian et al 1997).…”
Section: Resultsmentioning
confidence: 95%
See 4 more Smart Citations
“…These DMPP‐induced reductions probably reflect the appearance of a small degree of endplate ion channel block. However, given that the reductions in time constants of decay were small and similar for both MEPCs and EPCs, we consider it unlikely that the presence of this endplate ion channel block would have a significant impact on the quantal analysis of ACh release (see also Tian et al 1997).…”
Section: Resultsmentioning
confidence: 95%
“…Firstly, effects of channel block on current amplitudes are only detected in association with large decreases in the decay time constants of the signals (Prior et al 1990), something not seen here. Secondly, driving function analysis has shown that, under the conditions employed here, small amounts of endplate ion channel block equally affect MEPC and EPC amplitudes and so do not affect the analysis of ACh release (Tian et al 1997). Finally, the accumulation of DMPP‐blocked endplate channels during repetitive 50 Hz stimulation cannot underlie the differential effects of the compound on EPC and MEPC amplitudes since this would be expected to depress EPCs more than MEPCs and hence produce an apparent decrease in evoked ACh release.…”
Section: Discussionmentioning
confidence: 98%
See 3 more Smart Citations